The Activities of the Rostov-On-Don Anti-Plague Institute of the Rospotrebnadzor in the XXIst Century (on the occasion of the 90th anniversary of the Institute) - A. K. Noskov; M. V. Poleeva; O. F. Kretenchuk; E. I. Markovskaya; V. A. Korshenko; D. A. Osadchy; O. S. Chemisova (Проблемы особо опасных инфекций)
The aim of the work was to perform a brief overview of the data on the development, the main tasks of the Federal State Institution of Health “Rostov-on-Don Research Anti-Plague Institute of the Federal Service for Surveillance on Consumers’ Rights Protection and Human Wellbeing (Rospotrebnadzor) and its contribution to ensuring the sanitary and epidemiological welfare of the population of the Russian Federation. The review is based on the analysis of the reports on research work, archive materials and literature sources. Currently, priority and promising areas of research at the Institute are: epidemiological monitoring of cholera pathogens and natural-focal infections with an assessment of epidemiological risks and threats based on advanced methods of detection and identification of agents; development of measures aimed at preventing the spread of infections; epizootiological survey of natural foci of particularly dangerous infections; development of predictive modeling risk assessment systems, new techniques and approaches to improve laboratory diagnostics and epidemiological surveillance; development of sequencing; modernization of monitoring, including using molecular biological methods, and control of infectious diseases using geo-information technologies; transition to genomic epidemiological surveillance; improvement of unified online databases, creation of technologically independent, unified software platforms for bioinformatic analysis of the results of genome-wide sequencing; research of genetic markers of antibiotic resistance, as well as immunopathogenetic aspects of the course of particularly dangerous and other infections; ensuring interaction with all interested services and agencies in organizing and conducting events within the framework of sanitary protection of the territory. Relying on the vast experience of predecessors and stateof-the-art knowledge, the Rostov-on-Don Research Anti-Plague Institute of the Rospotrebnadzor actively takes part in solving topical issues to scientifically and practically support the provision of sanitary-epidemiological well-being and biological safety of the population of the Russian Federation.